Hyperkalemia Mimicking Anteroseptal Myocardial Infarction - Nugraha, Raka Aldy; Husen, Auliya; Muliawan, Hary Sakti; Zamroni, Dian (Jurnal Kardiologi Indonesia, 2023)
Background: Hyperkalemia often results in cardiac emergency associated with fatal cardiac arrhythmias. However, the presence of ST segment elevation in hyperkalemia is rare and could potentially subject the patients to unnecessary risk of intervention. Most commonly, ST elevation in hyperkalemia presents in a down-sloping fashion compared to the typical convex or upsloping pattern in myocardial infarction. However, in some cases, the ST elevation morphology can be very identical and difficult to distinguish. Herein, we describe a hyperkalemic patient presenting with non-ischemic ST segment elevation that resolved spontaneously following therapy. Case illustration: A 77-year-old, bed-ridden, inarticulate woman was admitted to emergency department with acute dyspnea perceived for 1.5 hours. The patient’s past clinical history included craniotomy for subdural hematoma, poorly controlled hypertension, hypertensive heart disease, rheumatoid arthritis, and dementia and was under candesartan, amlodipine, nebivolol, spironolactone, and atorvastatin treatment. The 12-lead electrocardiography (ECG) recording showed wide QRS complex with left bundle branch block pattern, slow atrial fibrillation with total atrioventricular block, ST segment elevation and Q wave in anteroseptal leads, and peaked T wave (Figure 1A). The pattern of ST elevation was indistinguishable from that of myocardial infarction which necessitated further laboratory confirmation. Laboratory results showed severe hyperkalemia (K+ 7.93 mmol/L) and normal troponin level (45.0 ng/L). The patient was given serial insulin-based therapy and calcium gluconate immediately. The follow-up ECG pictured normal sinus rhythm with no sign of bundle branch block, resolution of ST segment elevation, and reduction in T wave amplitude (Figure 1B). However, the reduction in potassium level was not significant and the patient also experienced an acute kidney injury. The patient was transferred to intensive care unit and was prepared for hemodialysis. Conclusion: ST segment elevation is a rare feature of hyperkalemia that could mislead the patient’s treatment. Thorough ECG evaluation is the key to narrow down the differential diagnosis. Every deviant feature should not be interpreted separately. Laboratory tests could help confirm the diagnosis, particularly in patients with atypical presentation and could help avoid unnecessary risk of intervention.This article has a related Erratum.